Making Ripples A Guidebook to Challenge Status Quo in OER Creation - Schilling, Kaitlin (Open textbook library., 2023)
Making Ripples: A Guidebook to Challenge Status Quo in OER Creation is a short resource designed to expand your understanding of inequities in the educational systems through breaking down the work into smaller pieces with opportunities for you to reflect, identify strategies for action, and locate resources and community members to connect with. The purpose of this guide is to explore strategies for you as OER creators to incorporate equitable practices into your workflows.